2021
DOI: 10.3389/fimmu.2021.737076
|View full text |Cite
|
Sign up to set email alerts
|

Sanguisorbae Radix Suppresses Colorectal Tumor Growth Through PD-1/PD-L1 Blockade and Synergistic Effect With Pembrolizumab in a Humanized PD-L1-Expressing Colorectal Cancer Mouse Model

Abstract: Immune checkpoints such as programmed death-1 (PD-1) have been proven as antitumor targets by enhancing cytotoxic T cell activity. All immune checkpoint blockades are antibody therapeutics that have large size and high affinity, as well as known immune-related side effects and low responses. To overcome the limitation of antibody therapeutics, we have explored PD-1/PD-L1 (programmed death-ligand 1) blockades in traditional oriental medicine, which has a long history but has not yet studied PD-1/PD-L1 blockades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Moreover, natural products have shown promises as immunomodulatory agents. Studies have shown that compared to ICIs alone, the combination of ICIs and natural products can exert synergistic effects on CRC by promoting antigen presentation, enhancing CD8 + T cell cytotoxic activity, increasing T cell infiltration and so on ( Liu et al, 2020b ; Liu et al, 2020c ; Lee et al, 2021 ; Xu et al, 2021 ). This may be a new strategy to transform “cold” tumours into “hot” tumours.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, natural products have shown promises as immunomodulatory agents. Studies have shown that compared to ICIs alone, the combination of ICIs and natural products can exert synergistic effects on CRC by promoting antigen presentation, enhancing CD8 + T cell cytotoxic activity, increasing T cell infiltration and so on ( Liu et al, 2020b ; Liu et al, 2020c ; Lee et al, 2021 ; Xu et al, 2021 ). This may be a new strategy to transform “cold” tumours into “hot” tumours.…”
Section: Introductionmentioning
confidence: 99%
“…One Ginseng-derived nanoparticle reprograms TAMs to increase chemokine (C-C motif) ligand 5 (CCL5) and CXCL9 secretion to recruit CD8 + T cells, which synergizes with anti-PD-1 [ 84 ]. Sanguisorbae Radix efficiently enhances tumor-infiltrating CD8 + T cell activation by blocking the PD-1/PD-L1 interaction in colorectal cancer (CRC), promoting the efficacy of anti-PD-1 [ 86 ]. Salviaric acid B, another active ingredient in salvia, potentiates CD8 + T cell infiltration in the TME along with endothelial protection resulting in the normalization of vascular function and inducing a positive efficacy of anti-PD-L1 in breast carcinoma models [ 87 ].…”
Section: Tcm Enhances the Efficacy Of Icis And Reverses Drug Resistancementioning
confidence: 99%
“…Hollandsworth et al 97 verified that near-infrared photoimmunotherapy is an effective method for the treatment of CRC using humanized mice. To overcome the limitations of antibody therapy for immune checkpoint blockade, Lee et al 98 explored a novel blockade in traditional oriental medicine, called Sanguisorbae Radix extract (SRE). They demonstrated that SRE alone has anticancer effects via immune checkpoint blockade and that the combination therapy of SRE and pembrolizumab has enhanced immuno-oncologic effects.…”
Section: Drug Testingmentioning
confidence: 99%